If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 5 = -16 Reorder the terms: 5 + 7x = -16 Solving 5 + 7x = -16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 7x = -16 + -5 Combine like terms: 5 + -5 = 0 0 + 7x = -16 + -5 7x = -16 + -5 Combine like terms: -16 + -5 = -21 7x = -21 Divide each side by '7'. x = -3 Simplifying x = -3
| 4+6x-12-5x=-12x+10x+9+4 | | 13x=5y | | k^2+8k+10=0 | | -8=5x+7 | | (x+5)(3x-2)(23x)=0 | | 5x+2=x+7 | | -x+15+3x+15=-4 | | x^2-x=-1.5 | | 11x^3+13x^2-6x=0 | | -1.1x-4=0.8 | | 3x+8+5x+6x=10x+5+8+3x | | (9+8i)-(-7+i)= | | 3x^2+8x=9+2x | | 2c+5(2c+3)= | | 11x^2-9=0 | | 4-3x=-12 | | x^2+18x= | | 2(-2)-3(0)=6 | | 14-8=34 | | 5=3(1)+2 | | 3(6)-4(-7)=5 | | 2x+4x+6x= | | 3d+4(d+2)= | | 4y-8x+12=0 | | 3k+14=(-2k)-31 | | 3(2x-1)=20 | | 4(5m+6)=64 | | (-7x^6y)(-4x^5y^2)= | | x-3y=-7 | | 2(x+5)+2x=x+16 | | 8-9x=56-37x | | x^2-59x-96=0 |